Karyotype Differentiation in Cultivated Chickpea Revealed by Oligopainting Fluorescence in situ Hybridization - Doležalová, Alžběta; Sládeková, Lucia; Šimoníková, Denisa; Holušová, Kateřina; Karafiátová, Miroslava; Varshney, Rajeev K.; Doležel, Jaroslav; Hřibová, Eva (Frontiers in Plant Science, 2022)
Chickpea (Cicer arietinum L.) is one of the main sources of plant proteins in the Indian subcontinent and West Asia, where two different morphotypes, desi and kabuli, are grown. Despite the progress in genome mapping and sequencing, the knowledge of chickpea genome at chromosomal level, including the long-range molecular chromosome organization, is limited. Earlier cytogenetic studies in chickpea suffered from limited number of cytogenetic landmarks and did not permit to identify individual chromosomes in the metaphase spreads or to anchor pseudomolecules to chromosomes in situ. In this study, we developed a system for fast molecular karyotyping for both morphotypes of cultivated chickpea. We demonstrate that even draft genome sequences are adequate to develop oligo-FISH barcodes for identification of chromosomes and comparative analysis among closely related chickpea genotypes. Our results show the potential of oligo-FISH barcoding for identification of structural changes in chromosomes, which accompanied genome diversification among chickpea cultivars. Moreover, oligo-FISH barcoding in chickpea pointed out some problematic, most probably wrongly assembled regions of the pseudomolecules of both, kabuli and desi reference genomes. Thus, oligo-FISH appears as a powerful tool not only for comparative karyotyping, but also for validation of genome assemblies.